Application of Faber polynomials to approximate solution of the Riemann problem - Pylak, D.; Sheshko, M. A.; Wójcik, P. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
In the paper, Faber polynomials are used to derive an approximate solution of the Riemann problem on a Lyapunov curve.Moreover, an estimation of the error of the approximated solution is presented and proved.